Effectiveness of Polyclonal Antibody Immunoconjugate Treatment with Propamidine Isethionate for Amoebic Keratitis in Golden Hamsters - Manuel Enrique Ávila-Blanco; Sandra Lizbeth Aguilera-Martínez; Javier Ventura-Juarez; Jorge Pérez-Serrano; Elizabeth Casillas-Casillas; Luis Fernando Barba-Gallardo (Journal of Parasitology Research)
Acanthamoeba griffini is known to cause amoebic keratitis (AK); its main causes are inadequate hygiene when contact lenses are handled and/or its prolonged use at night, as well as the use of contact lenses during underwater activities. The most used treatment for AK is the combination of propamidine isethionate combined with polyhexamethylene biguanide, which disrupts the cytoplasmic membrane, and damages cellular components and respiratory enzymes. We proposed an immunoconjugate treatment obtained from Acanthamoeba immunized rabbit serum combined with propamidine isethionate; the corneas of hamsters inoculated with A. griffini (MYP2004) were treated with the combined, at 1, 2, and 3 weeks. Propamidine isethionate is frequently used for AK treatment, in vivo study we are found IL-1β and IL-10 expression and caspase 3 activity is significantly increased with respect to the group that was inoculated with the amoeba without receiving any treatment, suggesting that it may be an effect of the toxicity of this drug on the corneal tissue. Application of the immunoconjugate showed enhanced amoebicidal and anti-inflammatory activities, with comparison to propamidine isethionate only. The aim of this study is to evaluate the effect of the immunoconjugate of propamidine isethionate and polyclonal antibodies as a treatment of AK in golden hamsters (Mesocricetus auratus).